Strategi Image Repair PT HM SAMPOERNA TBK pada peristiwa ‘karyawan pabrik Surabaya positif covid-19’ - Muhammad Ramzy Hasibuan; Irwansyah Irwansyah (Program Studi Ilmu Komunikasi, 2020)
The use of Image Repair Theory for companies during crisis communication is an interesting study. It is also applied when several PT HM Sampoerna Tbk factory employees are known to have died due to suffering from COVID-19. This event affected the company's image, especially the negative sentiment on the quality of the products produced due to employees affected by COVID-19. This study analyzes the image repair strategy used by PT HM Sampoerna Tbk through press releases published on the company's official website. The research objective is to analyze message options for organizations to use in times of crisis. The study uses a qualitative content analysis method by analyzing text written in press releases, then putting it into categories that have been determined in the image repair strategy. The results showed PT HM Sampoerna Tbk's inconsistency in using the Reducing Offensiveness strategy, which is often used in types of accident and/or challenge crises, including product damage situations. Excessive use of Reducing Offensiveness must be an organization's concern when conducting crisis communication, especially when the audience has a critical view of the organization. Reducing Offensiveness can be more optimally used by neutral third parties than the organization itself; however, the research results show that PT HM Sampoerna Tbk carries out all strategy delivery.